DIFFERENTIATED INSTRUCTION APPROACHES FOR ELEMENTARY SCHOOL STUDENTS: A REVIEW OF CURRENT EDUCATIONAL LITERATURE - Muhammad Raka Anantama; Muhammad Reza Azizu Romadhon (CV. Fahr Publishing, 2025)
This study aims to explore the implementation and effectiveness of differentiated instruction (DI) strategies in elementary education, with particular emphasis on addressing diverse student needs across multiple subjects and classroom contexts. The research employs a systematic literature review methodology, synthesizing peer-reviewed studies published within the last five years to identify trends, challenges, and outcomes associated with DI in primary schools. Key findings indicate that formative assessment, structured teacher planning, flexible grouping, and tailored instructional materials significantly enhance student engagement, learning outcomes, and inclusivity. However, persistent challenges include limited teacher training, insufficient time for lesson preparation, lack of institutional support, and resource constraints, which often impede optimal DI implementation. This study contributes novelty by providing a cross-curricular, multi-dimensional perspective, integrating teacher planning, student products, and engagement measures into a cohesive framework, and examining DI in both mainstream and under-resourced elementary contexts. The results highlight the critical role of teacher professional development and school support structures in sustaining DI practices, offering insights into how differentiated strategies can be systematically applied to improve equity and learning outcomes globally. In conclusion, differentiated instruction represents a promising approach for enhancing educational quality and student-centered learning in primary classrooms; its effective implementation requires both pedagogical competence and institutional facilitation, and the findings of this study offer actionable guidance for teachers, policymakers, and curriculum designers.